In search of the lost «Lógos». On Martin Heidegger’s «Was ist das - die Philosophie?» - Gilabert Bello, Fernando (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
Martin Heidegger’s text Was ist das - die Philosophie? is one of the key works to make a hermeneutic of his thought. In it he explains how what philosophy originally intended has no correlation with its conquests throughout tradition, which are rather tinged with a rationalist tint that obviates the affective states, so necessary for understanding philosophical thinking. In this way, we return with Heidegger to go back to the beginning of philosophy, until Heraclitus, so that you can establish some guidelines that help us in our disquisitions within philosophy. To do so, it will be necessary to take up again the true Greek sense of λὀγος as it was proposed by Heraclitus: how to flow and how to fight.